Politisasi Agama dalam Pemilu 2024 di Indonesia: Tantangan dan Strategi Pencegahan - Nur Triyono (Ashfiya Journal of Qualitative Insight in Islamic Studies, 2025)
This study examines the politicization of religion in the 2024 elections in Indonesia. Several instances of religious politicization, such as the case of Ahok's blasphemy and the dissolution of HTI, have triggered societal polarization and threatened governmental stability. The aim of this paper is to prevent religious politicization in the  elections by implementing various prevention strategies. Through mapping the phenomena of religious politicization that have occurred, the author analyzing prevention strategies that encompass enhancing individual knowledge, influencing policies and legislation, and changing organizational practices. It is hoped that this research will contribute to preventing religious politicization in future elections, thereby preserving the sustainability of democracy and social stability in Indonesia.